PENDIDIKAN SEKS: APAKAH PERLU DISAMPAJKAN KEPADA REMAJA? - Hari Arnirullah Rahrnan Hari Arnirullah Rahrnan; Eddy Purnomo Eddy Purnomo (Jurnal Cakrawala Pendidikan, 1999)
Who actually has the duty of delivering sex educationto adolescents? It is not easy to decide who should give sexeducation and how it should be given, because many stilldo not know what sex education really is and how it is implemented.All this time many have assumed that sex is always relatedto coition, reproduction, health, and morals. Some thinkthat sex is something "dirty" and something not proper to be taught in class. This happens because often the thoughts.feelings, and images of sex are obtained from limited andnarrow life experiences. Many receive sex education fromparents, kiends, electronic media, relatives, etc. in variousways that are mostly traditional and incomprehensive. Acomprehensive scope of sex education should cover sociological.psychological, and biological aspects. Every aspecthas other aspects which involve feelings, early concepts,inter-personal relationships, and decisioribmaking. T'neseaspects should be viewed as supporting each other to makea whole and complete sexuality.Understanding sexuality as a totality existing in manwill contribute to the favorable formation of adolescent personalityand encourage responsible inter-personal relationships.Thus, there will be formed in adolescents a system ofvalues which will control their behavior in interacting withtheir environment.